Analysis of Code-Mixing Patterns in English Students Daily Conversation - Apriani Sarce Mince Kalasuat; Rizqi Claudia Wardani.H; Nurteteng (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study investigated the patterns of code-mixing used by students of the UNIMUDA English Department in daily conversational interactions and the factors influencing its use. A descriptive qualitative design was applied. The data were collected through naturalistic observation, questionnaires, and interviews involving five active students. The conversational data were analyzed using thematic analysis and categorized based on Muysken’s (2000) code-mixing theory.The findings showed that three patterns of code-mixing occurred: intra- sentential code-mixing, inter-sentential code-switching, and tag switching. Intra- sentential code-mixing was the most dominant pattern, as participants frequently inserted English lexical items into Indonesian sentence structures to maintain fluency and efficiency. Inter-sentential switching was used to clarify meaning and emphasize ideas, while tag switching functioned as a pragmatic marker in interaction. The study also revealed that code-mixing was influenced by internal factors, namely language identity and language proficiency, and external factors, including social situation and communicative purpose. Among these factors, communicative purpose was the most dominant, as code-mixing helped participants achieve clarity, emphasis, and smooth communication. Overall, code- mixing functioned as a strategic communicative practice rather than merely a linguistic habit.